Patient Ethnicity Affects Triage Assessments and Patient Prioritization in U.S. Department of Veterans Affairs Emergency Departments - Vigil, Jacob M. (Medicine (Baltimore), 2016)
Ethnic minority patients receive lower priority triage assignments in Veteran's Affairs (VA) emergency departments (EDs) compared to White patients, but it is currently unknown whether this disparity arises from generalized biases across the triage assessment process or from differences in how objective and/or subjective institution-level or person-level information is incorporated into the triage assessment process, thus contributing to disparate treatment. The VA database of electronic medical records of patients who presented to the VA ED from 2008 to 2012 was used to measure patient ethnicity, self-reported pain intensity (PI) levels, heart rate (HR), respiratory rate (RR), and nurse-provided triage assignment, the Emergency Severity Index (ESI) score. Multilevel, random effects linear modeling was used to control for demographic and clinical characteristics of patients as well as age, gender, and experience of triage nurses. A total of 359,642 patient/provider encounters between 129,991 VA patients and 774 nurses were included in the study. Patients were 61% non-Hispanic White [NHW], 28% African-American, 7% Hispanic, 2% Asian-American, <1% American Indian/Alaska Native, and 1% mixed ethnicity. After controlling for demographic characteristics of nurses and patients, African-American, Hispanic, and mixed-ethnicity patients reported higher average PI scores but lower HRs and RRs than NHW patients. NHW patients received higher priority ESI ratings with lower PI when compared against African-American patients. NHW patients with low to moderate HRs also received higher priority ESI scoring than African-American, Hispanic, Asian-American, and Mixed-ethnicity patients; however, when HR was high NHWs received lower priority ESI ratings than each of the minority groups (except for African-Americans). This study provides evidence for systemic differences in how patients’ vital signs are applied for determining ESI scores for different ethnic groups. Additional prospective research will be needed to determine how this specific person-level mechanism affects healthcare quality and outcomes.